Development of Pisces Diversity E-Module based on Fish Identification Research in Plalangan Village, Jember - Nasution, Nanda Eska Anugrah; Sofyan, Moch (Indonesian Journal of Mathematics and Natural Science Education, 2024)
Integrating the local potential as a learning resource is a vital component of the curriculum to guarantee that learning is both practical and relevant. Transforming biodiversity identification data from students' environments into learning media may improve students' understanding of biodiversity by providing them with a deeper insight into the contextual aspects of biodiversity. Thus, it is essential to design an electronic module for pisces diversity in the village of Plalangan Kalisat that includes fish identification outcomes.The aims of this study are as follows: to ascertain the validity of the pisces diversity e-module product containing fish identification results in the developed village of Plalangan Kalisat; and to determine the practicality of the aforementioned product in the developed village of Plalangan Kalisat. This study used the Lee & Owens (2004) development model. The product validation conducted by material experts yielded an average percentage of 89.83% (highly valid), by media specialists yielded an average percentage of 89.78% (highly valid), by Indonesian language experts yielded an average percentage of 92.22% (highly valid), and by biology teachers yielded an average percentage of 93.33% (highly valid). The small group trial yielded an average percentage of 92.83% (highly appealing). The findings from the large group trial revealed an average score of 94.91% (highly appealing). Based on these two test results, it can be concluded that the developed e-Module has proven to be valid and practical.